Power losses reduction of power transmission network using optimal location of low-level generation - Marwa M. Marei; Manal H. Nawer (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Due to the growth of demand for electric power, electric power loss reduction takes great attention for the power utility. In this paper, a low-level generation or Distributed Generation (DG) has been used for transmission power losses reduction. Karbala city transmission network (which is the case study) has been represented by using MATLAB m-file to study the load flow and the power loss for it. The paper proposed the Particle Swarm Optimization (PSO) technique in order to find the optimal number and allocation of DG with the objective to decrease power losses as possible. The results show the effect of the optimal allocation of DG on power loss reduction.